(untitled) (American Journal of Business Management, Economics and Banking, 2023)
Nowadays, the problem of solving many issues in rural areas is horizontal. These issues are social, ecological, demographic, economic, cultural and educational. In order to solve these issues, there is a need for highly qualified personnel in all fields in the villages. It is impossible to be a good specialist without fundamental mathematical knowledge. It is known from experience that conducting practical training with a rich mathematical-nature connection leads to deep satisfaction. For example, for course requirements, the connection between mathematics and construction sciences can be achieved in practical exercises on the topic "Derivative and its applications", or the role of mathematics in agriculture and farms can be demonstrated in the activity "Calculation of the surfaces of flat figures".